DNA barcoding of economically important freshwater fish species from north‐central Nigeria uncovers cryptic diversity. Issue 14 (13th June 2018) - Iyiola, Oluyinka A.; Nneji, Lotanna M.; Mustapha, Moshood K.; Nzeh, Chioma G.; Oladipo, Segun O.; Nneji, Ifeanyi C.; Okeyoyin, Agboola O.; Nwani, Christopher D.; Ugwumba, Obih A.; Ugwumba, Adiaha A. A.; Faturoti, Emmanuel O.; Wang, Yun‐yu; et al.
Abstract: This study examines the utility of morphology and DNA barcoding in species identification of freshwater fishes from north‐central Nigeria. We compared molecular data (mitochondrial cytochrome c oxidase subunit I ( COI ) sequences) of 136 de novo samples from 53 morphologically identified species alongside others in GenBank and BOLD databases. Using DNA sequence similarity‐based (≥97% cutoff) identification technique, 50 (94.30%) and 24 (45.30%) species were identified to species level using GenBank and BOLD databases, respectively. Furthermore, we identified cases of taxonomic problems in 26 (49.00%) morphologically identified species. There were also four (7.10%) cases of mismatch in DNA barcoding in which our query sequence in GenBank and BOLD showed a sequence match with different species names. Using DNA barcode reference data, we also identified four unknown fish samples collected from fishermen to species level. Our Neighbor‐joining (NJ) tree analysis recovers several intraspecific species clusters with strong bootstrap support (≥95%). Analysis uncovers two well‐supported lineages within Schilbe intermedius . The Bayesian phylogenetic analyses of Nigerian S. intermedius with others from GenBank recover four lineages. Evidence of genetic structuring is consistent with geographic regions of sub‐Saharan Africa. Thus, cryptic lineage diversity may illustrate species' adaptive responses to local environmental conditions. Finally, our study underscores the importance of incorporating morphology and DNA barcoding in species identification. Although developing a complete DNA barcode reference library for Nigerian ichthyofauna will facilitate species identification and diversity studies, taxonomic revisions of DNA sequences submitted in databases alongside voucher specimens are necessary for a reliable taxonomic and diversity inventory. Abstract : We compared molecular data (mitochondrial cytochrome c oxidase subunit I (COI) sequences) of 136 de novo samples from 53 morphologically identified species alongside others in GenBank and BOLD databases. Using DNA sequence similarity‐based (≥97% cutoff) identification technique, 50 (94.30%) and 24 (45.30%) species were identified to species level using GenBank and BOLD databases respectively. Furthermore, we identified cases of taxonomic problems in 26 (49.00%) morphologically identified species. Using DNA barcode reference data, we also identified four unknown fish samples collected from fishermen to species level. Our Neighbor‐joining (NJ) tree analysis recovers several intraspecific species clusters with strong bootstrap support (≥95%). Analysis uncovers two well supported lineages within Schilbe intermedius. The Bayesian phylogenetic analyses of Nigerian S. intermedius with others from GenBank recover four lineages. Evidence of genetic structuring is consistent with geographic regions of sub‐Saharan Africa. Thus, cryptic lineage diversity may illustrate species' adaptive responses to local environmental conditions.